Investigation of chloride stress corrosion cracking in austenitic stainless steel - Mohamad Khairuazlan, Kamaruzaman (2013)
Chloride stress corrosion cracking (CSCC) of AISI 304 austenitic stainless steel are the most important corrosion processes that affect the performance of this stainless steel. SCC occurs when susceptible material under the stress is exposed to a specific environment such as corrosive environment. Since austenitic stainless steel are widely used in power boiler, nuclear power, chemical plant and marine industry, SCC can cause a major losses to these industry. The purpose of this project is to study the effect of chloride stress corrosion cracking in austenitic stainless steel based on the sensitization treatment of the specimens and different concentration mixtures of sulphuric acid and sodium chloride. Method use in this study was weight loss method. From the measurement and experiment result, it shows that mass loss for specimens with sensitization treatments is higher than mass loss for specimens without sensitization treatment. The experimental result also indicates that SCC occurs only at certain concentration mixtures of sulphuric acid and sodium chloride. This was confirmed by using scanning electron microscope and digital weighing balance.